Transient cerebral ischemia induces albumin expression in microglia only in the CA1 region of the gerbil hippocampus - Park, Joon Ha (Mol Med Rep, 2017)
Albumin, the most abundant plasma protein, is known to exhibit a neuroprotective effect in animal models of focal and global cerebral ischemia. In the present study, the expression and immunoreactivity of albumin was examined in the hippocampus following 5 min of transient cerebral ischemia in gerbils. Albumin immunoreactivity was observed in microglia of the CA1 hippocampal region 2 days post-ischemic insult, and it was significantly increased at 4 days following ischemia-reperfusion. In addition, at 4 days post-ischemic insult, albumin-immunoreactive microglia were abundant in the stratum pyramidale of the CA1 region. The present results demonstrated that albumin was newly expressed post-injury in microglia in the CA1 region, suggesting ischemia-induced neuronal loss. Albumin expression may therefore be associated with ischemia-induced delayed neuronal death in the CA1 region following transient cerebral ischemia.